PENGARUH MINUM JUS ANGGUR DAN JUS JAMBU BIJI DENGAN DAN TANPA GULA TERHADAP PERUBAHAN PH SALIVA - Ratnawati Hendari; Irma HY Siregar (Odonto : Dental Journal, 2014)
Background: Saliva pH is the standard indicator used to describe the alkalinity or acidity of the saliva which could be changed by dietary (sugar), mechanically or chemically stimuli from food or beverages consumed. Grapes and guava fruit are often used as beverage. The purpose of this study was to determine the effect of drinking one of grape or guava juice with and without sugar to PH of saliva changes. Method: The research method used in this study was a quasi experiment with cross sectional approach. The study was conducted on 40 college students which were divided into 4 groups, i.e. groups of grape juice with and without sugar and guava juice drink groups with and without sugar. Juice was made with electric juicer with 200 g of fruit mixed with 450 ml of water for groups without sugar and added 50 g of white sugar for groups with sugar. The volume of juice to drink was 50 ml. Salivary pH was measured using pH strips and performed before and 2 minutes after drinking the juice. Results: The results showed that there was an increase in the pH of saliva after drinking the juice in all treatment groups (p <0.05), except in grape juice with sugar, but salivary pH changes among the treatments were similar (p = 0.252). Conclusion: The conclusion of this study was grape juice and guava juice with and without sugar could increased the pH of saliva. except grape juice with sugar. but between treatment groups there was no difference in salivary pH changes